Laminate and method for producing the same, packaging bag and package

The laminate structure with a solvent-free adhesive layer containing a polyisocyanate derivative of hexamethylene diisocyanate addresses the issues of discoloration and peeling in digital printing laminates during heat sealing, achieving enhanced heat resistance and reduced environmental impact.

JP2025051060APending Publication Date: 2025-04-04TOPPAN HOLDINGS INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023159962
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Digital printing using electrostatic ink compositions in laminates for packaging bags results in weak cohesive force and adhesive strength, leading to discoloration and peeling issues during heat sealing, especially when using conventional solvent-free adhesive compositions.

Method used

A laminate structure comprising a substrate film, a primer layer, an adhesive layer with a solvent-free composition containing a polyol component and a polyisocyanate component, including a derivative of hexamethylene diisocyanate, and a sealant film, which enhances the heat resistance and adhesive strength while reducing environmental impact.

Benefits of technology

The proposed laminate structure effectively suppresses discoloration and peeling during heat sealing, maintaining the exterior appearance and ensuring excellent heat resistance, while also reducing environmental impact due to the use of a solvent-free adhesive.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051060000001_ABST
    Figure 2025051060000001_ABST
Patent Text Reader

Abstract

To provide a laminate having reduced discoloration or peeling of the laminate which occurs when heat sealing while reducing environmental load.SOLUTION: There is provided a laminate having a base material film, a primer layer, an adhesive layer and a sealant film in this order, which has a printed surface of an electrostatic ink composition adhered to the adhesive layer, wherein the adhesive layer contains a solvent-free type adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof or a mixture thereof, the polyisocyanate component contains a hexamethylene diisocyanate derivative and when the sealant film is heat sealed under the prescribed heat sealing conditions, the color difference (ΔE) obtained by the following expression (A) is less than 3.0. In the expression (A), ΔL* indicates the difference in brightness before and after heating and pressing under the heat sealing conditions and both Δa* and Δb* indicate the difference in hue and saturation before and after heating and pressing under the heat sealing conditions.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a laminate and a manufacturing method thereof, a packaging bag, and a package. [Background technology]

[0002] Packaging bags for containing and sealingly storing beverages, foodstuffs, and the like are known. Packages using thin films or sheets are used as packaging bags. Various information such as product, brand, manufacturer, and the like is printed on such packaging bags. As a means for such printing, a digital printer using an electrostatic ink composition is known.

[0003] For example, Patent Document 1 proposes applying a primer resin to a first flexible substrate such as a PET film to obtain a coating surface, performing electrostatic printing on the coating surface using a digital printer (Indigo 20000 label and packaging digital printer manufactured by HP), and applying a crosslinking composition. It is known that such a laminate containing an electrostatic ink layer produced by digital printing has a reduced adhesive strength. Therefore, Patent Document 2 proposes using a cured product of a polyol, a polyisocyanate, and an epoxy compound as an adhesive layer as a laminate capable of maintaining a sufficiently high adhesive strength between each layer even under high-temperature hot water conditions such as retort treatment. Patent Document 3 also discloses a laminate in which a cured product of a polyol, a polyisocyanate, and an epoxy compound is used as an adhesive layer, which suppresses discoloration during heat sealing and has excellent heat resistance.

[0004] On the other hand, from the viewpoint of reducing the environmental load, adhesives that do not contain organic solvents are being developed. For example, Patent Document 4 proposes a two-component curing solventless adhesive containing a polyisocyanate component and a polyol component, and a composite film for packaging foods, beverages, medicines, quasi-drugs, etc. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2018-530478 [Patent Document 2] International Publication No. 2021 / 024981 [Patent Document 3] JP 2022-102513 A [Patent Document 4] JP 2011-162656 A Summary of the Invention [Problem to be solved by the invention]

[0006] Digital printing using an electrostatic ink composition allows for small lot production, and therefore digitally printed laminates are used for various packaging bags. However, in laminates in which the printed surface of an electrostatic ink composition is bonded using a conventional solvent-free adhesive composition to reduce environmental impact, the cohesive force of the electrostatic ink layer is weak, and the printed surface may be discolored by heat from heat sealing. In addition, since the electrostatic ink layer has a weak cohesive force and a low adhesive strength, when the printed surface of electrostatic printing is bonded using a conventional solvent-free adhesive composition, the printed surface may peel off due to heat from heat sealing, and peeling of the laminate may occur on the surface.

[0007] In view of this, the present disclosure provides a laminate having an electrostatic ink layer, which has excellent heat resistance while reducing the environmental impact, and a manufacturing method thereof. Also provided is a packaging bag and a packaging body having such a laminate, which are sufficiently suppressed in discoloration and peeling of the laminate. [Means for solving the problem]

[0008] One aspect of the present disclosure provides a laminate comprising a base film, a primer layer, an adhesive layer, and a sealant film in this order, and comprising a printed surface of an electrostatic ink composition adhered to the adhesive layer, wherein the adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component comprises a derivative of hexamethylene diisocyanate, and when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, the laminate has a color difference (ΔE) calculated by the following formula (A) of less than 3.0.

[0009]

number

[0010] Electrostatic ink compositions produced by digital printers tend to have inferior heat resistance and strength compared to other inks. Therefore, when the sealant film of a laminate having a printed surface of an electrostatic ink composition is heated and pressurized under a specified heat seal condition, it tends to discolor easily. However, the adhesive layer of the laminate that adheres to the printed surface of the electrostatic ink composition contains a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component contains a derivative of hexamethylene diisocyanate, so that discoloration can be suppressed when the laminate is heat sealed under a specified heat seal condition.

[0011] It is believed that the hexamethylene diisocyanate derivative contained in the polyisocyanate component in the adhesive layer has a tendency to easily penetrate or become compatible with the electrostatic ink layer. This is believed to have the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink composition, and the effect of improving the adhesive strength of the adhesive layer. Therefore, when heated and pressed under a specified heat sealing condition, it is possible to suppress the occurrence of gaps near the printed surface and the breakage of the electrostatic ink composition. Therefore, it is possible to sufficiently suppress discoloration due to the occurrence of gaps and breakage of the electrostatic ink composition at the sealed portion when heat sealed, and to make the color difference (ΔE) less than 3.0. Furthermore, since the adhesive layer of the above laminate is a solvent-free type, it is possible to reduce the environmental load.

[0012] One aspect of the present disclosure is a laminate comprising a base film, an adhesive layer, and a sealant film in this order, and comprising a printed surface of an electrostatic ink composition adhered to the adhesive layer, wherein the adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, and a cured product thereof, or a mixture thereof, the polyisocyanate component comprises a derivative of hexamethylene diisocyanate, and when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220° C., a pressure of 0.2 MPa, and a time of 1.5 seconds, the number of discoloration points having a size of 20 μm or more that are generated is 1 mm 2 or less per 1 mm 2 of the heat-sealed portion. 2 The laminate has 10 or less particles per unit area.

[0013] The electrostatic ink composition produced by a digital printer tends to have inferior heat resistance and strength compared to other inks. Therefore, when the sealant film of a laminate having a printed surface of the electrostatic ink composition is heated and pressurized under a specified heat sealing condition, it tends to discolor easily. However, the adhesive layer of the laminate that adheres to the printed surface of the electrostatic ink composition contains a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component contains a derivative of hexamethylene diisocyanate, so that the occurrence of discoloration points when the laminate is heat-sealed under a specified heat sealing condition can be suppressed.

[0014] It is believed that the hexamethylene diisocyanate derivative contained in the polyisocyanate component in the adhesive layer has a tendency to easily penetrate or become compatible with the electrostatic ink layer. This is believed to have the effect of agglomerating the electrostatic ink composition to improve its strength, and the effect of improving the adhesive strength of the adhesive layer. For this reason, when heated and pressed under heat-sealing conditions, it is possible to suppress the occurrence of gaps near the printed surface and the breakage of the electrostatic ink composition. Therefore, discoloration due to the occurrence of gaps and breakage of the electrostatic ink composition in the sealed portion when heat-sealed is sufficiently suppressed, and the number of discoloration points having a size of 20 μm or more per 1 mm of the heat-sealed portion is reduced. 2 The number of defects per unit area can be reduced to 10 or less. Furthermore, since the adhesive layer of the laminate is a solvent-free type, the environmental load can be reduced.

[0015] One aspect of the present disclosure provides a laminate comprising a base film, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, wherein the adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, and a cured product thereof, or a mixture of these, and the polyisocyanate component comprises a derivative of hexamethylene diisocyanate, and when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, the area ratio of the peeled portion of the laminate based on the heat-sealed portion is 9.0% or less.

[0016] The printed surface of the electrostatic ink composition printed by a digital printer tends to have poorer heat resistance and strength than other inks. Therefore, when the sealant film of the laminate having the printed surface of the electrostatic ink composition is heated and pressurized under a specified heat sealing condition, the laminate at the heat sealed portion tends to peel off easily. However, the above laminate has an adhesive layer that adheres to the printed surface of the electrostatic ink composition, which contains a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component contains a derivative of hexamethylene diisocyanate, and the area ratio of the peeled portion of the laminate based on the heat sealed portion that occurs when the laminate is heat sealed under a specified heat sealing condition is 9.0% or less. Therefore, by using such an adhesive layer, peeling of the laminate when the laminate is heat sealed can be suppressed, and a laminate that maintains its appearance even when the laminate is heat sealed can be obtained.

[0017] It is considered that the hexamethylene diisocyanate derivative contained in the polyisocyanate component in the adhesive layer tends to easily penetrate or become compatible with the electrostatic ink layer. This is considered to have the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink composition, and the effect of improving the adhesive strength of the adhesive layer. Therefore, when heat sealing is performed, it is possible to suppress the occurrence of gaps near the printed surface, the breakage of the electrostatic ink composition, and the peeling of the adhesive layer. Therefore, the area ratio of the peeled part of the laminate based on the heat seal part that occurs when the laminate is heat sealed is 9.0% or less, and the occurrence of peeling of the laminate can be sufficiently suppressed. Furthermore, since the adhesive layer of the laminate is a solvent-free type, it is possible to reduce the environmental load.

[0018] One aspect of the present disclosure provides a method for producing a laminate, the method comprising the steps of: forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition, wherein the polyisocyanate component includes a derivative of hexamethylene diisocyanate; and when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, the color difference (ΔE) calculated by the following formula (A) is less than 3.0.

[0019]

number

[0020] Electrostatic ink compositions produced by digital printers tend to have inferior heat resistance and strength compared to other inks. Therefore, when the sealant film of a laminate having a printed surface of an electrostatic ink composition is heated and pressurized under a specified heat seal condition, it tends to discolor easily. However, the adhesive layer of the laminate that adheres to the printed surface of the electrostatic ink composition contains a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component contains a derivative of hexamethylene diisocyanate, so that discoloration can be suppressed when the laminate is heat sealed under a specified heat seal condition.

[0021] It is believed that the hexamethylene diisocyanate derivative contained in the polyisocyanate component in the adhesive layer has a tendency to easily penetrate or become compatible with the electrostatic ink layer. This is believed to have the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink composition, and the effect of improving the adhesive strength of the adhesive layer. Therefore, when heated and pressed under a specified heat sealing condition, it is possible to suppress the occurrence of gaps near the printed surface and the breakage of the electrostatic ink composition. Therefore, it is possible to sufficiently suppress discoloration due to the occurrence of gaps and breakage of the electrostatic ink composition at the sealed portion when heat sealed, and to make the color difference (ΔE) less than 3.0. Furthermore, since the adhesive layer of the above laminate is a solvent-free type, it is possible to reduce the environmental load.

[0022] One aspect of the present disclosure is a method for producing a sealant film comprising the steps of: forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition, wherein the polyisocyanate component includes a derivative of hexamethylene diisocyanate, and the number of discoloration points having a size of 20 μm or more that are produced when the substrate is heated and pressurized under heat-sealing conditions of a temperature of 220° C., a pressure of 0.2 MPa, and a time of 1.5 seconds is 1 mm 2 of a heat-sealed portion. 2The present invention provides a method for producing a laminate in which the number of particles per unit area is 10 or less.

[0023] Electrostatic ink compositions produced by digital printers tend to have poorer heat resistance and strength than other inks. For this reason, when the sealant film of a laminate having a printed surface of an electrostatic ink composition is heated and pressed under a specified heat sealing condition, it tends to discolor easily. However, on the other hand, the above laminate has an adhesive layer that adheres to the printed surface of the electrostatic ink composition, which contains a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component contains a derivative of hexamethylene diisocyanate, and can suppress the occurrence of discoloration points having a size of 20 μm or more that occur when the laminate is heat sealed under a specified heat sealing condition. By using such an adhesive layer, the number of discoloration points in the electrostatic ink layer when the laminate is heat sealed can be reduced.

[0024] It is believed that the hexamethylene diisocyanate derivative contained in the polyisocyanate component in the adhesive layer has a tendency to easily penetrate or become compatible with the electrostatic ink layer. This is believed to have the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink composition, and the effect of improving the adhesive strength of the adhesive layer. For this reason, when heated and pressed under heat-sealing conditions, it is possible to suppress the occurrence of gaps near the printed surface and the breakage of the electrostatic ink composition. Therefore, discoloration due to the occurrence of gaps and breakage of the electrostatic ink composition in the sealed portion when heat-sealed is sufficiently suppressed, and the number of discoloration points having a size of 20 μm or more can be reduced by 1 mm per 1 mm of the heat-sealed portion. 2 The number of defects per unit area can be reduced to 10 or less. Furthermore, since the adhesive layer of the laminate is a solvent-free type, the environmental load can be reduced.

[0025] One aspect of the present disclosure provides a method for producing a laminate, comprising the steps of: forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition containing a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition, wherein the polyisocyanate component contains a derivative of hexamethylene diisocyanate, and when heated and pressed under heat-sealing conditions at a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, the area ratio of the peeled portion of the laminate based on the heat-sealed portion is 9.0% or less.

[0026] The printed surface of the electrostatic ink composition printed by a digital printer tends to have poorer heat resistance and strength than other inks. Therefore, when the sealant film of the laminate having the printed surface of the electrostatic ink composition is heated and pressurized under a specified heat sealing condition, the laminate at the heat sealed portion tends to peel off easily. However, the above laminate has an adhesive layer that adheres to the printed surface of the electrostatic ink composition, which contains a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof, and the polyisocyanate component contains a derivative of hexamethylene diisocyanate, and the area ratio of the peeled portion of the laminate based on the heat sealed portion that occurs when the laminate is heat sealed under a specified heat sealing condition is 9.0% or less. Therefore, by using such an adhesive layer, peeling of the laminate when the laminate is heat sealed can be suppressed, and a laminate that maintains its appearance even when the laminate is heat sealed can be obtained.

[0027] It is considered that the hexamethylene diisocyanate derivative contained in the polyisocyanate component in the adhesive layer tends to easily penetrate or become compatible with the electrostatic ink layer. This is considered to have the effect of agglomerating the electrostatic ink composition to improve the strength of the electrostatic ink composition, and the effect of improving the adhesive strength of the adhesive layer. Therefore, when heat sealing is performed, it is possible to suppress the occurrence of gaps near the printed surface, the breakage of the electrostatic ink composition, and the peeling of the adhesive layer. Therefore, the area ratio of the peeled part of the laminate based on the heat seal part that occurs when the laminate is heat sealed is 9.0% or less, and the occurrence of peeling of the laminate can be sufficiently suppressed. Furthermore, since the adhesive layer of the laminate is a solvent-free type, it is possible to reduce the environmental load.

[0028] One aspect of the present disclosure provides a packaging bag formed by heat-sealing the sealant films in the laminate described above. The packaging bag has the laminate described above, and thus has a solvent-free adhesive layer, and is sufficiently suppressed from discoloring the heat-sealed portion and peeling of the laminate when heat-sealed. Therefore, a packaging bag having excellent heat resistance while reducing environmental impact can be provided. Such a packaging bag can be suitably used for packaging bags such as zipper bags, standing bags, and gusset bags that have areas that are easily exposed to heat and are prone to discoloration or peeling of the laminate. In addition, digital printing (electrostatic printing) can be used, and therefore the degree of freedom in designing the package can be sufficiently increased.

[0029] One aspect of the present disclosure provides a package comprising the above-mentioned packaging bag and an item to be contained in the packaging bag. The above-mentioned packaging has the above-mentioned laminate, and thus has a solvent-free adhesive layer, while discoloration of the heat-sealed portion and peeling of the laminate when heat-sealed are sufficiently suppressed. Therefore, a package having excellent heat resistance while reducing environmental load can be provided. Such a package can be suitably used for packages having areas that are easily exposed to heat and are prone to discoloration or peeling of the laminate, such as standing bags, zipper bags, and gusset bags. In addition, digital printing (electrostatic printing) can be used, so the degree of freedom in designing the package can be sufficiently increased. Effect of the Invention

[0030] The present invention provides a laminate having an electrostatic ink layer, which has excellent heat resistance while reducing the environmental impact, and a method for producing the same. It is also possible to provide a packaging bag and a packaging body that include such a laminate and are sufficiently suppressed in discoloration and peeling of the laminate. [Brief description of the drawings]

[0031] [Figure 1] FIG. 2 is a cross-sectional view showing an example of a laminate. [Diagram 2] 1 is an optical microscope photograph showing an enlarged view of the surface of a laminate after heat sealing. [Diagram 3] FIG. 2 is a plan view of an example of a laminate in which delamination occurred after heat sealing. [Figure 4] FIG. 4 is a cross-sectional view showing another example of a laminate. [Diagram 5] FIG. 2 is a plan view showing an example of a packaging bag and a packaging body. [Figure 6] FIG. 2 is a plan view showing an example of a zipper bag. [Figure 7] FIG. 2 is a plan view showing an example of a standing bag. [Figure 8] FIG. 11 is a perspective view showing another example of a packaging bag. [Figure 9] 1 is an enlarged photograph of the surface of a heat-sealed portion after the laminate of Example 7 was heat-sealed. [Figure 10] 1 is an enlarged photograph of the surface of a heat-sealed portion after the laminate of Comparative Example 7 was heat-sealed. [Figure 11] 1 is a photograph of the surface of a heat-sealed portion after the laminate of Comparative Example 8 was heat-sealed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Hereinafter, an embodiment of the present disclosure will be described with reference to the drawings as needed. However, the following embodiment is an example for explaining the present disclosure, and is not intended to limit the present disclosure to the following content. In the description, the same reference numerals are used for the same elements or elements having the same functions, and redundant description is omitted as the case may be. In addition, the positional relationship such as up, down, left, right, etc. is based on the orientation of the reference numerals shown in the drawings, unless otherwise specified. Furthermore, the dimensional ratio of each element is not limited to the ratio shown in the drawings.

[0033] Unless otherwise specified, the materials exemplified in this disclosure can be used alone or in combination of two or more. When there are multiple substances corresponding to each component in the composition, the content of each component in the composition means the total amount of the multiple substances present in the composition, unless otherwise specified. In this disclosure, a numerical range indicated using "~" indicates a range including the respective numerical values ​​described before and after "~" as the minimum and maximum values. In this disclosure, the upper limit and lower limit values ​​indicated individually can be arbitrarily combined.

[0034] <Laminate> Fig. 1 is a cross-sectional view showing an example of a laminate. Fig. 1 shows a cross section along the lamination direction (thickness direction) of the laminate. The laminate 300 has a base film 10, a primer layer 40, an electrostatic ink layer 50, an adhesive layer 30, and a sealant film 20, in this order. The primer layer 40 and the electrostatic ink layer 50 are in contact with each other, and the electrostatic ink layer 50 and the adhesive layer 30 are in contact with each other.

[0035] The substrate film 10 may have a flexible substrate. The flexible substrate may include, for example, one or both of a metal foil such as an aluminum foil and a thermoplastic polymer in the form of a film. Flexible substrates include films of biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), oriented polyamide (OPA), solid polypropylene (CPP), linear low density polyethylene (LLDPE), low density polyethylene (LDPE), and nylon.

[0036] The base film 10 may include, for example, a vapor deposition film (transparent vapor deposition film) having a resin layer such as a PET film and a barrier layer (vapor deposition layer) on the resin layer. This can improve the sealing property when the laminate 300 is used as a packaging material. Examples of the barrier layer include a vapor deposition layer of a metal foil, a metal (e.g., aluminum) or a metal oxide (e.g., silica or alumina). The thickness of the base film 10 may be 7 to 150 μm, 10 to 100 μm, or 12 to 80 μm. A specific example of the transparent vapor deposition film is a transparent vapor deposition PET film in which a transparent vapor deposition layer is formed on a PET film. The base film 10 may include a nylon film such as a barrier nylon film.

[0037] The primer layer 40 may contain a resin. Examples of the resin include polyvinyl alcohol resin, cellulose-based resin, polyester, polyamine, polyethyleneimine resin, polyamide resin, polyurethane, polyacrylic polymer, hydroxyl-containing resin, carboxyl-containing resin, and amine-based polymer. By having the primer layer 40, printing of the electrostatic ink composition using a digital printer can be smoothly performed. In addition, the adhesion of the electrostatic ink layer 50 to the primer layer 40 can be improved. The application amount of the resin constituting the primer layer 40 is, for example, 0.01 to 1.5 g / m. 2 and may be 0.05 to 1.0 g / m 2 may be also possible.

[0038] The laminate 300 has a printing surface 52 on the primer layer 40. An electrostatic ink layer 50 is provided on the printing surface 52. The electrostatic ink layer 50 may be composed of an electrostatic ink composition. The electrostatic ink layer 50 is provided by electrostatic printing using a digital printing machine. As shown in FIG. 1, the electrostatic ink layer 50 may be provided so as to cover a part of the surface of the primer layer 40. That is, the electrostatic ink layer 50 may be provided so as to be interspersed between the primer layer 40 and the adhesive layer 30. This allows the laminate 300 to have blank areas.

[0039] The electrostatic ink layer 50 may be of a single color, or may be formed by laminating a plurality of electrostatic ink compositions having different colors. The electrostatic ink layer 50 and the adhesive layer 30 are adjacent to each other. In this example, the heights of the plurality of electrostatic ink layers 50 are the same, but this is not limited thereto. The electrostatic ink layer 50 may be a plurality of layers, or may be continuous into one layer. In this example, the electrostatic ink layer 50 is interrupted in the lateral direction of FIG. 1. The interrupted portion of the electrostatic ink layer 50 becomes a blank portion. In another example, the electrostatic ink layer 50 may be formed without interruption, and the laminate may have no portion where the adhesive layer 30 and the primer layer 40 are in direct contact with each other.

[0040] The thickness of the electrostatic ink layer 50 can be adjusted by changing the ink coverage. The ink coverage represents the ratio of the dot area per unit area. For example, when a certain area is uniformly printed in a single color, the ink coverage is 100%. On the other hand, the ink coverage of an area where no printing is performed (plain area) is 0%. The ink coverage can be calculated based on these two. For example, the ink coverage can be 200% when the ink is applied once, and 300% when the ink is applied twice. In this way, the ink coverage can be increased by increasing the number of times the ink is applied. When only half of the entire area is printed once, the ink coverage is 50%. When printing is performed using ink of multiple colors, the ink coverage can be calculated for each color ink, and the total of the ink coverages can be used as the ink coverage of the target electrostatic ink layer 50. The ink coverage is set by a digital printer (e.g., HP's Indigo 20000 label and packaging digital printer) and can be adjusted by specifying a desired value in the ink coverage setting. The ink coverage on the printing surface 52 can be confirmed by observing the printing surface 52 with an optical microscope.

[0041] The ink coverage of the electrostatic ink layer 50 may be 500% or less, 400% or less, or 300% or less. By having the ink coverage in this range, the adhesive strength of the electrostatic ink layer 50 can be improved while the freedom of design can be improved by using a plurality of inks. The ink coverage of the electrostatic ink layer 50 may be 0% or more, 10% or more, 100% or more, or 200% or more. By having the ink coverage of the electrostatic ink layer 50 in this range, the freedom of design of the package can be further improved. The range of the ink coverage may be, for example, 0 to 500%, 10 to 500%, 100 to 400%, or 100 to 300%.

[0042] The electrostatic ink layer 50 on the printing surface 52 may be comprised of circular dots of an electrostatic ink composition. By varying the size of the dots, the color intensity on the printing surface 52 can be adjusted.

[0043] The electrostatic ink composition constituting the electrostatic ink layer 50 is an ink composition used in liquid electrophotographic printing, i.e., electrostatic printing, and is printed on the primer layer 40. The electrostatic ink composition may contain a colorant or pigment such as a dye, and a resin. In addition to these, the electrostatic ink composition may also contain a carrier fluid or carrier liquid. It may further contain a charge director, a charge adjuvant, a surfactant, a viscosity modifier, an emulsifier, and other additives. It may also contain a component that permeates through the adhesive layer 30 (e.g., a polyisocyanate component).

[0044] Examples of colorants include cyan pigments, magenta pigments, yellow pigments, and black pigments. From the viewpoint of facilitating digital printing, a resin having a relatively low melting point (for example, 100° C. or less) can be used as the resin. Examples of the resin include thermoplastic resins such as ethylene acrylic acid copolymer, propylene acrylic acid copolymer, ethylene methacrylic acid copolymer, propylene methacrylic acid copolymer, and ethylene vinyl acetate copolymer. It is preferable that the resin contains at least one of ethylene acrylic acid copolymer and ethylene methacrylic acid copolymer.

[0045] Carrier fluids and carrier liquids include hydrocarbons, silicone oils, vegetable oils, and the like. Hydrocarbons include aliphatic hydrocarbons, branched aliphatic hydrocarbons, and aromatic hydrocarbons, and the like. The electrostatic ink composition, when printed onto a print substrate, such as a first substrate, may be substantially free of carrier liquid. The carrier liquid may be removed, for example, by an electrophoretic process or evaporation during printing, thereby transferring substantially only solids to the print substrate.

[0046] Charge directors serve to maintain a sufficient electrostatic charge on the particles contained in the electrostatic ink composition and include, for example, ionic compounds such as metal salts of fatty acids, metal salts of sulfosuccinates, metal salts of oxyphosphates, metal salts of alkylbenzenesulfonic acids, metal salts of aromatic carboxylic or aromatic sulfonic acids, as well as zwitterionic and non-ionic compounds such as polyoxyethylenated alkylamines, lecithin, polyvinylpyrrolidone, and organic acid esters of polyhydric alcohols.

[0047] The charge adjuvant has the effect of increasing or stabilizing the charge of particles contained in the electrostatic ink composition. Examples of the charge adjuvant include barium petronate, calcium petronate, naphthenic acid Co salt, naphthenic acid Ca salt, naphthenic acid Cu salt, naphthenic acid Mn salt, naphthenic acid Ni salt, naphthenic acid Zn salt, naphthenic acid Fe salt, stearate Ba salt, stearate Co salt, stearate Pb salt, stearate Zn salt, stearate Al salt, stearate Cu salt, stearate Fe salt, and metal carboxylates.

[0048] The electrostatic ink composition may contain a crosslinked product crosslinked by components contained in the adhesive layer 30 and / or the primer layer 40. This can sufficiently increase the strength of the electrostatic ink layer 50 itself, as well as the adhesive strength between the printing surface 52 and the electrostatic ink layer 50, and between the electrostatic ink layer 50 and the primer layer 40. In addition, during heat sealing, it is possible to prevent the dots constituting the electrostatic ink layer 50 from moving and the occurrence of gaps at the interface between the electrostatic ink layer 50 and the adhesive layer 30. This can sufficiently prevent discoloration and peeling of laminated portions due to heat sealing.

[0049] The laminates 300 and 310 have a color difference of less than 3.0 when the sealant films 20 are heated and pressed together under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, with the color difference before heat-sealing as a reference. In this disclosure, the "color difference (ΔE)" is a measured value calculated from the measurements of a spectrophotometer (e.g., eXact (device name) manufactured by X-rite). A specific calculation procedure will be described below using the laminate 300 as an example.

[0050] A laminate 300 having a printing surface 52 of an electrostatic ink composition is prepared. The lightness (L * ), hue and saturation (a * , b * ) is measured.

[0051] Thereafter, the laminate 300 is heated and pressed from the surface 300A side under the above heat sealing conditions using a heat sealing device. Before and after the heating and pressing, the lightness (L * ), hue and saturation (a * , b * The measurement position of the surface 300A is the same before and after heating and pressing by the heat sealing device. The difference in brightness (ΔL * ), the difference in hue and saturation (Δa * , Δb * ), the color difference (ΔE) is calculated by the following formula (A). The color difference calculated in this way is the "color difference (ΔE)" in this disclosure.

[0052]

number

[0053] The color difference may be less than 3.0, may be 2.5 or less, or may be 2.0 or less, from the viewpoint of sufficiently suppressing discoloration during heat sealing. The lower limit of the color difference may be 0.1 or more, or may be 0.3 or more, from the viewpoint of ease of production. The color difference can be increased by increasing the temperature and pressure during heat sealing or increasing the heat sealing time. Conversely, the color difference can be decreased by decreasing the temperature and pressure during heat sealing or shortening the heat sealing time. The color difference can be adjusted by adjusting the heat sealing conditions in this way.

[0054] When the surface 300A is viewed in plan, the coverage rate of the electrostatic ink layer 50 with respect to the entire region (area) to be measured for color difference may be 50 area% or more, 70 area% or more, or may be 100 area%. This coverage rate of 100 area% means that the entire region to be measured for "color difference" is covered by the electrostatic ink layer 50. This coverage rate of 50 area% means that half of the region to be measured for "color difference" is covered by the electrostatic ink layer 50. In the laminate 300 of FIG. 1, the coverage rate of the electrostatic ink layer 50 with respect to the entire region (area) to be measured for "color difference" is approximately 55 area%.

[0055] The reason why the color difference before and after heat sealing can be reduced is believed to be that the specific components contained in the adhesive layer 30 have the effect of agglomerating the electrostatic ink composition of the electrostatic ink layer 50 to improve the strength of the electrostatic ink layer 50 itself, and the effect of improving the adhesive strength between the electrostatic ink layer 50 and the layer adjacent thereto. This makes it possible to prevent gaps from occurring at the interfaces between the electrostatic ink layer 50 and the adhesive layer 30 and the primer layer 40, the electrostatic ink layer 50 from moving and deforming, and the electrostatic ink layer 50 from breaking. This makes it possible to prevent discoloration due to the occurrence of gaps, deformation, and breakage, and to sufficiently prevent discoloration of the printed surface 52.

[0056] Fig. 2 is an optical microscope photograph showing an enlarged view of the heated and pressurized surface of the laminate when the surface on the base film side is heated and pressurized under predetermined heat sealing conditions. In Fig. 2, discoloration points 55 are generated in the halftone dots 53 (electrostatic ink layer) on the heated and pressurized surface of the laminate. These discoloration points 55 indicate that gaps are generated at the interface between the halftone dots 53 and the adhesive layer 30, or that the halftone dots 53 are deformed. The discoloration points 55 may be caused by air bubbles at the interface.

[0057] When the laminate 300 is heated and pressed from the surface 300A side under heat sealing conditions of a temperature of 220° C., a pressure of 0.2 MPa, and a time of 1.5 seconds, the strength of the electrostatic ink layer 50 composed of halftone dots is sufficiently high, and the adhesive strength between the electrostatic ink layer 50 and the adhesive layer 30 is sufficiently high, so that discoloration points 55 as shown in Fig. 3 can be sufficiently reduced. 2 (=1.0mm x 1.0mm) area, when heated and pressurized under the above heat sealing conditions, the heat seal part is 1mm 2 The number of discoloration points having a size of 20 μm or more occurring per unit area is preferably 10 or less, more preferably 6 or less, and even more preferably 3 or less. By reducing the discoloration points 55 in this way, it is possible to more sufficiently suppress color unevenness occurring during heat sealing. The number of discoloration points having a size of 20 μm or more is determined by drawing a circumscribing circle of the discoloration points 55 as shown in FIG. 3 and counting the points having a diameter of 20 μm or more. In the present disclosure, a discoloration point is a point where the shape, size, color, etc. of a halftone dot changes to a degree that can be detected when comparing before and after heating and pressurization and observing a magnified image with an optical microscope (magnification: 100 times) with the naked eye.

[0058] The number of discoloration points can be increased by increasing the temperature and pressure during heat sealing or by lengthening the heat sealing time. Conversely, the number of discoloration points can be decreased by decreasing the temperature and pressure during heat sealing or by shortening the heat sealing time. In this way, the number of discoloration points can be adjusted by adjusting the heat sealing conditions.

[0059] When the laminate 300 is heated and pressed from the surface 300A side under heat sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, the area ratio of the peeled part of the laminate on the surface of the base film 10 side based on the heat seal part may be 9.0% or less. The area ratio of the peeled part of the laminate based on the heat seal part may be 6.0% or less, or may be 3.0% or less. When the area ratio of the peeled part of the laminate is within this range, the effect of heat on the laminate 300 can be sufficiently reduced, and the adhesive strength and appearance of the laminate after heat sealing can be maintained in a preferable state.

[0060] The area ratio of the peeled part of the laminate can be increased by increasing the temperature and pressure during heat sealing or by lengthening the heat sealing time. Conversely, the area ratio of the peeled part of the laminate can be decreased by decreasing the temperature and pressure during heat sealing or by shortening the heat sealing time. In this way, the area ratio of the peeled part of the laminate can be adjusted by adjusting the heat sealing conditions.

[0061] The area of ​​the peeled portion L of the laminate can be calculated using a digital microscope (microscope) at the heat-sealed heat-sealed portion X. If necessary, it may be calculated using image processing. When the peeled portion L of the laminate occurs at multiple locations, the area of ​​the peeled portion L of the laminate that occurs can be calculated one by one using the above-mentioned procedure, and the total of the areas can be calculated as the peeled portion of the laminate. For example, as shown in FIG. 3, when three peeled portions L1, L2, and L3 of the laminate occur at the heat-sealed portion X, the total area of ​​L1, L2, and L3 can be used as the area of ​​the peeled portion L of the laminate at the heat-sealed portion X. The area of ​​the peeled portion L of the laminate thus obtained is divided by the total area of ​​the heat-sealed portion X to calculate the area ratio of the peeled portion of the laminate based on the heat-sealed portion.

[0062] The thickness of the adhesive layer 30 may be 0.5 to 5 μm, 0.6 to 3 μm, or 0.8 to 2 μm, thereby achieving a good balance between adhesive strength and design.

[0063] The thickness of each layer constituting the laminate 300 can be measured by observing a cross section of the laminate 300 with a digital microscope.

[0064] The adhesive layer 30 may be composed of a solventless adhesive composition, a cured product thereof, or a mixture thereof. The adhesive composition may be of a two-component curing type. The adhesive layer 30 contains two components, a polyisocyanate component and a polyol component. These components may at least partially react with each other to form a cured product. The cured product may contain polyurethane. The adhesive layer 30 containing the above two components and the electrostatic ink layer 50 are in direct contact with each other.

[0065] The polyisocyanate component contains a hexamethylene diisocyanate derivative (hereinafter, sometimes referred to as an "HDI derivative"). This increases the cohesive force of the electrostatic ink layer 50, increases the adhesive strength of the adhesive layer 30, and reduces the effect of heat on the electrostatic ink layer 50 when heat-sealed. The HDI derivative may be a bifunctional derivative of hexamethylene diisocyanate. The HDI derivative is an aliphatic diisocyanate, and is more likely to penetrate into the electrostatic ink layer 50 than aromatic diisocyanates. This allows the electrostatic ink layer 50 and the adhesive layer 30 to blend well with each other, improving the crosslinking effect of the adhesive layer 30 and the electrostatic ink layer 50. This improves the adhesion between the electrostatic ink layer 50 and the adhesive layer 30.

[0066] The HDI derivative may be a trifunctional derivative of HDI (hexamethylene diisocyanate). Such a trifunctional derivative penetrates the electrostatic ink layer 50 and crosslinks with the components of the electrostatic ink layer 50. This increases the cohesive force of the electrostatic ink layer 50, and further increases the adhesive strength of the laminate 300. By including both a bifunctional derivative and a trifunctional derivative as the HDI derivative, the HDI derivative can be sufficiently penetrated into the electrostatic ink layer 50 and the crosslinking reaction with the components of the electrostatic ink layer 50 can be further advanced, so that even if the electrostatic ink layer 50 is thick, the adhesive strength of the adhesive layer 30 can be maintained sufficiently high, and the influence of heat during heat sealing can be further reduced.

[0067] In the adhesive layer 30 (adhesive composition), the content of the trifunctional derivative of HDI may be higher than the content of the bifunctional derivative of HDI. This allows a crosslinking reaction to proceed in the adhesive layer 30 and the electrostatic ink layer 50, improving the strength of the adhesive layer 30 and the electrostatic ink layer 50, and allowing the adhesive force between the adhesive layer 30 and the electrostatic ink layer 50 to be sufficiently increased. Therefore, the influence of heat during heat sealing can be further reduced. From this viewpoint, the mass ratio of the trifunctional derivative to the total of the bifunctional derivative and the trifunctional derivative may be 55 mass% or more, or may be 60 mass% or more. On the other hand, from the viewpoint of maintaining the flexibility of the adhesive layer 30 and the electrostatic ink layer 50, the mass ratio of the trifunctional derivative to the total of the bifunctional derivative and the trifunctional derivative may be 85 mass% or less, 80 mass% or less, or 75 mass% or less. An example of the mass ratio of the trifunctional derivative to the total of the bifunctional derivative and the trifunctional derivative is 55 to 85 mass%.

[0068] Examples of HDI derivatives include HDI multimers (e.g., dimers, trimers, pentamers, heptamers, etc.), biuret modified products (e.g., biuret modified products produced by the reaction of HDI with water, tertiary alcohols, or amines), allophanate modified products (e.g., allophanate modified products produced by the reaction of HDI with alcohols), urea modified products (e.g., urea modified products produced by the reaction of HDI with diamines), oxadiazinetrione (e.g., oxadiazinetrione produced by the reaction of HDI with carbon dioxide), carbodiimide modified products (carbodiimide modified products produced by decarboxylation condensation reaction of HDI), polyol modified products, etc. Also, an adduct of HDI and trimethylolpropane may be used.

[0069] The content of the HDI derivative in the polyisocyanate component may be 15% by mass or more, 20% by mass or more, or 25% by mass or more. This allows the above-mentioned effects to be fully exhibited. The content of the HDI derivative in the polyisocyanate component may be 60% by mass or less, 50% by mass or less, or 40% by mass or less. An example of the content of the HDI derivative in the polyisocyanate component is 15 to 60% by mass.

[0070] The polyisocyanate component may further contain a polyisocyanate having two or more isocyanate groups in one molecule, which is different from the HDI derivative. This allows the laminate 300 to be flexibly designed according to the desired properties. Examples of such polyisocyanate monomers include aromatic diisocyanates, aromatic alicyclic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates.

[0071] Aromatic diisocyanates are highly reactive and easily cured, which allows the laminate 300 to be rapidly manufactured. Examples of aromatic aliphatic diisocyanates include m- or p-phenylene diisocyanate or a mixture thereof, 2,4- or 2,6-tolylene diisocyanate or a mixture thereof (TDI), 4,4'-, 2,4'-, or 2,2'-diphenylmethane diisocyanate or a mixture thereof (MDI), 4,4'-toluidine diisocyanate (TODI), 4,4'-diphenyl ether diisocyanate, 4,4'-diphenyl diisocyanate, 1,5-naphthalene diisocyanate (NDI), and the like.

[0072] Examples of the aromatic aliphatic diisocyanate include 1,3- or 1,4-xylylene diisocyanate or a mixture thereof (XDI), 1,3- or 1,4-tetramethylxylylene diisocyanate or a mixture thereof (TMXDI), ω,ω'-diisocyanato-1,4-diethylbenzene, and the like.

[0073] Examples of the aliphatic diisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, pentamethylene diisocyanate, 1,2-, 2,3- or 1,3-butylene diisocyanate, 2,4,4- or 2,2,4-trimethylhexamethylene diisocyanate, and the like.

[0074] Examples of alicyclic diisocyanates include 1,3-cyclopentene diisocyanate, 1,4-cyclohexane diisocyanate, 1,3-cyclohexane diisocyanate, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate; IPDI), 4,4'-, 2,4'-, or 2,2'-dicyclohexylmethane diisocyanate or a mixture thereof (hydrogenated MDI), methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 1,3- or 1,4-bis(isocyanatomethyl)cyclohexane or a mixture thereof (hydrogenated XDI), and the like.

[0075] The polyisocyanate component may contain a derivative of the polyisocyanate monomer (polyisocyanate derivative). Examples of the polyisocyanate derivative include polyisocyanate derivatives (e.g., dimers, trimers, pentamers, heptamers, etc.), allophanate modified products (e.g., allophanate modified products produced by the reaction of a polyisocyanate monomer with alcohols, etc.), biuret modified products (e.g., biuret modified products produced by the reaction of a polyisocyanate monomer with water or amines, etc.), urea modified products (e.g., urea modified products produced by the reaction of a polyisocyanate monomer with a diamine, etc.), oxadiazinetrione (e.g., oxadiazinetrione produced by the reaction of a polyisocyanate monomer with carbon dioxide gas, etc.), and carbodiimide modified products (carbodiimide modified products produced by decarboxylation condensation reaction of a polyisocyanate monomer, etc.).

[0076] The polyisocyanate component may include an isocyanate-terminated prepolymer. The isocyanate-terminated prepolymer is a urethane prepolymer having at least two isocyanate groups at the molecular end. The urethane prepolymer can be obtained by subjecting at least one member selected from the group consisting of a polyisocyanate monomer, a polyisocyanate derivative, and an isocyanate-terminated prepolymer to a urethane reaction with a polyol.

[0077] The polyol component may contain at least one selected from the group consisting of polyester polyols and polyether polyols. Among these, from the viewpoint of reducing production costs and suppressing hydrolysis, polyether polyol may be contained.

[0078] The polyether polyol may be a polyalkylene oxide. For example, it may be obtained by addition reaction of an alkylene oxide such as ethylene oxide and / or propylene oxide with a low molecular weight polyol as an initiator. Specific examples include polyethylene glycol, polypropylene glycol, and polyethylene polypropylene glycol (random or block copolymer). In addition, for example, polytetramethylene ether glycol obtained by ring-opening polymerization of tetrahydrofuran may be mentioned.

[0079] The polyester polyol can be obtained, for example, by a condensation reaction or an ester exchange reaction between a polyhydric alcohol and a polybasic acid, its alkyl ester, its acid anhydride, or its acid halide. Examples of the polyhydric alcohol include a low molecular weight diol, a low molecular weight triol, and a low molecular weight polyol having four or more hydroxyl groups.

[0080] Examples of low molecular weight diols include ethylene glycol, propylene glycol, trimethylene glycol, 1,4-butylene glycol, 1,3-butylene glycol, 1,2-butylene glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2,2-dimethyl-1,3-propanediol, neopentyl glycol, 1,6-hexanediol, 2,2-diethyl-1,3-propanediol, 3,3-dimethylolheptane, and 2-ethyl-2-butyl-1,3-propanediol.

[0081] Examples of low molecular weight triols include glycerin, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-hydroxymethylpentane, 1,2,6-hexanetriol, trimethylolethane, trimethylolpropane, 2-methyl-2-hydroxymethyl-1,3-propanediol, 2,4-dihydroxy-3-(hydroxymethyl)pentane, and 2,2-bis(hydroxymethyl)-3-butanol.

[0082] Examples of low molecular weight polyols having four or more hydroxyl groups include tetramethylolmethane, pentaerythritol, dipentaerythritol, D-sorbitol, xylitol, D-mannitol, and D-mannite.

[0083] Examples of the alkyl ester of a polybasic acid include methyl ester and ethyl ester of a polybasic acid. Examples of the acid anhydride include acid anhydrides derived from a polybasic acid. For example, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, 2-alkyl (C12-18) succinic anhydride, tetrahydrophthalic anhydride, and trimellitic anhydride can be mentioned.

[0084] The acid halide may be an acid halide derived from the above-mentioned polybasic acid, such as oxalic acid dichloride, adipic acid dichloride, or sebacic acid dichloride.

[0085] In the adhesive layer 30 (adhesive composition), the mass ratio of the polyisocyanate component may be higher than the mass ratio of the polyol component. Specifically, the mass ratio of the polyisocyanate component to the polyol component may be 1 or more, 1.2 or more, or 1.4 or more. In this way, by increasing the mass ratio of the polyisocyanate component to the polyol component, the curing reaction is promoted and the adhesion and curing process can be sufficiently shortened. From the same viewpoint, the mass ratio of the polyisocyanate component to the polyol component may be 4 or less, or 3 or less. One example of the mass ratio of the polyisocyanate component to the polyol component is 1 to 4.

[0086] Examples of the sealant film 20 include a non-oriented polypropylene film (CPP film), a linear low-density polyethylene film (LLDPE film), and a low-density polyethylene film (LDPE). The thickness of the sealant film 20 may be 10 to 150 μm, 20 to 100 μm, or 30 to 80 μm.

[0087] FIG. 4 is a cross-sectional view showing another example of the laminate. FIG. 4 shows a cross-section along the lamination direction (thickness direction) of the laminate. The laminate 310 has a base film 10, a primer layer 40, an electrostatic ink layer 51, a first adhesive layer 30, an intermediate layer 21, a second adhesive layer 31, and a sealant film 20 in this order. The primer layer 40 and the electrostatic ink layer 51 are in contact with each other, and the electrostatic ink layer 51 and the adhesive layer 30 are in contact with each other. The electrostatic ink layer 51 is formed so as to cover the entire primer layer 40. Therefore, the laminate 310 does not have a plain portion. However, in a modified example, the electrostatic ink layer 51 may be interrupted like the electrostatic ink layer 50 of the laminate 300 in FIG. 1, and the laminate 310 may have a plain portion.

[0088] The intermediate layer 21 may have a flexible substrate. Examples of the flexible substrate include films of biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), oriented polyamide (OPA), and nylon (NY). The intermediate layer 21 may be, for example, a deposition film (transparent deposition film) including a resin layer such as a PET film and a barrier layer (deposition layer) on the resin layer, or may be a metal foil or a barrier film. Examples of the metal foil include aluminum foil.

[0089] The second adhesive layer 31 may have the same components and thickness as the adhesive layer 30 in Fig. 1. The material and thickness of the sealant film 20 may be as described for the sealant film 20 in the laminate 300 in Fig. 1. The other layers of the laminate 310 may be as described for the laminate 300 in Fig. 1.

[0090] The adhesive layer 30, the first adhesive layer 30, and / or the second adhesive layer 31 (adhesive composition) may contain a surface modifier that improves adhesion to the primer layer 40, the intermediate layer 21, and the sealant film 20. When the intermediate layer 21 is a barrier layer such as a metal, the adhesive strength and seal strength between the adhesive layer 30, 31 and the barrier layer can be further increased. When the barrier layer has a metal layer (aluminum layer) such as a metal foil (aluminum foil) or a metal film (aluminum film), the adhesive layer 30, 31 (adhesive composition) contains a surface modifier, thereby further improving adhesion to the metal layer.

[0091] Examples of the surface modifier include those containing at least one selected from sulfamic acid, phosphoric acid, nitric acid, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl methyl cellulose, and ethyl hydroxyethyl cellulose.

[0092] The adhesive composition constituting the adhesive layer 30 may contain optional components such as additives in addition to the polyisocyanate component and the polyol component. Examples of additives include antioxidants, ultraviolet absorbers, light stabilizers, fillers, silane coupling agents, epoxy resins, catalysts, coating property improvers, leveling agents, nucleating agents, lubricants, release agents, defoamers, plasticizers, surfactants, pigments, dyes, organic fine particles, inorganic fine particles, antifungal agents, and flame retardants. The adhesive composition is solvent-free and does not contain a solvent such as an organic solvent. This reduces the environmental load and sufficiently improves the working environment. The solvent-free adhesive composition is used by heating during coating.

[0093] The adhesive strength (lamination strength) of the laminate 300, 310 may be 1.0 N / 15 mm width or more, 1.5 N / 15 mm width or more, or 1.7 N / 15 mm width or more. The adhesive strength of the laminate 300, 310 mainly depends on the cohesive strength of the electrostatic ink layer 50 and the adhesive strength of the adhesive layers 30, 31. If the cohesive strength of the electrostatic ink layer 50 and the adhesive strength of the adhesive layers 30, 31 are high, the adhesive strength of the laminate 300, 310 can be sufficiently high. A packaging bag made of such a laminate 300, 310 can suppress the laminate 300, 310 from peeling off due to an external force applied when tearing. Therefore, the packaging bag can be opened cleanly. The adhesive strength (lamination strength) of the laminate 300, 310 may be 5.0 N / 15 mm width or less.

[0094] The adhesive strength in the present disclosure is a peel adhesive strength measured in accordance with the description of JIS K 6854-1: 1999. Specifically, it can be measured by the method described in the examples of the present disclosure.

[0095] The seal strength when the sealant films 20 of the laminates 300, 310 are bonded together may be 15.0 N / 15 mm width or more, 20.0 N / 15 mm width or more, or 25.0 N / 15 mm width or more. When the seal strength is in this range, a packaging bag and a packaging body having sufficiently high durability can be obtained. The seal strength can be measured in accordance with JIS K 7127:1999 "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets". The seal strength may be 100.0 N / 15 mm width or less. The range of the seal strength may be, for example, 15.0 to 100.0 N / 15 mm width, 20.0 to 100.0 N / 15 mm width, or 25.0 to 100.0 N / 15 mm width.

[0096] The laminate of the present disclosure is not limited to the structures of Figs. 1 and 4. For example, it may have the following laminate structure. In each example, the leftmost layer is the base film 10, and the rightmost layer is the sealant film 20. In each example, each layer is arranged in order from left to right. The following third adhesive layer may be the same adhesive layer as the adhesive layer 30 (first adhesive layer) and the second adhesive layer 31, or may be a different adhesive layer from these. The layer structure of the laminate is not limited to the following examples.

[0097] Example 1) PET film / primer layer / electrostatic ink layer / adhesive layer / LLDPE film (linear low-density polyethylene film) Example 2) Nylon film / primer layer / electrostatic ink layer / adhesive layer / LLDPE film Example 3) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / adhesive layer / CPP film (non-oriented polypropylene film) Example 4) Barrier nylon film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 5) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / first adhesive layer / PET film / second adhesive layer / CPP film Example 6) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / first adhesive layer / nylon film / second adhesive layer / CPP film Example 7) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / 1st adhesive layer / PET film / 2nd adhesive layer / nylon film / 3rd adhesive layer / CPP film Example 8) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / 1st adhesive layer / nylon film / 2nd adhesive layer / PET film / 3rd adhesive layer / CPP film Example 9) Transparent vapor-deposited PET film / primer layer / electrostatic ink layer / first adhesive layer / PET film / second adhesive layer / PET film / third adhesive layer / CPP film Example 10) OPP film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 11) OPP film / primer layer / electrostatic ink layer / adhesive layer / LLDPE film Example 12) Nylon film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 13) PET film / primer layer / electrostatic ink layer / adhesive layer / CPP film Example 14) PET film / primer layer / electrostatic ink layer / first adhesive layer / nylon film / second adhesive layer / LLDPE film Example 15) PET film / primer layer / electrostatic ink layer / first adhesive layer / aluminum foil / second adhesive layer / LDPE film Example 16) PET film / primer layer / electrostatic ink layer / first adhesive layer / aluminum foil / second adhesive layer / nylon film / third adhesive layer / LLDPE film

[0098] <Method of manufacturing laminate> An example of a method for producing a laminate is described below. In this example, a laminate 300 shown in Fig. 1 is produced. The method includes the steps of forming a primer layer 40 on one side of a base film 10, printing an electrostatic ink composition on the primer layer 40 to form an electrostatic ink layer 50 and obtain a printed surface 52, adhering the printed surface 52 to one side of the sealant film 20 using a solventless adhesive composition containing a polyisocyanate component and a polyol component, and curing or semi-curing the adhesive composition to form an adhesive layer 30.

[0099] The primer layer 40 may be formed on one side of the substrate film 10 by flexographic printing or gravure printing. The primer layer 40 may be formed by crosslinking a resin raw material with a crosslinking agent. Crosslinking may be performed by irradiating with ultraviolet light, heat, ionizing radiation such as an electron beam, or non-ionizing radiation such as microwave radiation. The printing of the electrostatic ink composition may be performed by electrostatic printing using a digital printer. As the digital printer, for example, the "Indigo 20000 label and packaging digital printer" manufactured by HP may be used. In this manner, the electrostatic ink layer 50 is formed, and the printing surface 52 is obtained.

[0100] The adhesive composition may be used to bond the printed surface 52 and one side of the sealant film 20 together as follows. For example, a roll coater made up of a combination of multiple rolls is used to apply the adhesive composition, which has been heated to about 40 to 90°C and melted, to the printed surface 52 of the base film 10 or one side of the sealant film 20. Thereafter, the adhesive composition and the lamination surface of the other base material are laminated together using a nip roll so that the adhesive composition on the printed surface 52 or the adhesive composition on the sealant film 20 faces the lamination surface of the other base material. The raw roll thus obtained is aged. The adhesive composition is cured by the aging process, and the adhesive layer 30 is formed. In this way, a laminate 300 can be produced that includes the base film 10, the primer layer 40, the electrostatic ink layer 50, the adhesive layer 30, and the sealant film 20 in this order. The aging temperature may be 20 to 50°C, and the aging time may be 0.5 to 5 days.

[0101] When manufacturing the laminate 310, the sealant film 20 is replaced with the intermediate layer 21 in the above-mentioned process, and the adhesive composition that has been heated to, for example, about 40 to 90°C and melted is further applied to the surface of the intermediate layer 21 opposite to the adhesive layer 30. The application of the adhesive composition here may also be performed by a roll coater combining a plurality of rolls. Thereafter, the applied adhesive composition and the sealant film 20 are bonded to each other using a nip roll so that the applied adhesive composition and the sealant film 20 face each other. The raw roll thus obtained is aged. The adhesive composition is cured or semi-cured by a urethane reaction by aging, and the second adhesive layer 31 containing a cured product is formed. Aging to obtain the first adhesive layer 30 and the second adhesive layer 31 may be performed simultaneously. In this way, the laminate 310 having the base film 10, the primer layer 40, the electrostatic ink layer 50, the first adhesive layer 30, the intermediate layer 21, the second adhesive layer 31, and the sealant film 20 in this order can be manufactured. The laminates according to the respective modified examples can be manufactured in the same manner as the laminates 300 and 310.

[0102] The laminates 300 and 310 thus manufactured have the configurations and properties as described above. The explanation of the laminates 300 and 310 and their modified examples also applies to the above-mentioned example of the manufacturing method.

[0103] The laminates 300, 310 have a printed surface 52 printed by digital printing (electrostatic printing), allowing for a sufficiently high degree of freedom in design. In addition, the use of a solvent-free adhesive composition allows for a sufficient reduction in environmental impact. And, even though such a solvent-free adhesive composition is used, the laminates 300, 310 have excellent heat resistance. Such laminates 300, 310 are suitable for use as packaging materials. The laminates 300, 310 may be used as packaging materials to produce packaging bags and packages.

[0104] <Packaging bags and packaging> FIG. 5 is a plan view showing an example of a packaging bag and a package formed using the above-mentioned laminate. The packaging bag 100 is formed by bonding the sealant films 20 of a pair of laminates 300 (310) together. The surface 300A on the base film 10 side becomes the outer surface of the packaging bag 100. The packaging bag 100 includes a sealed portion 101 formed by bonding the peripheries of a pair of film-like, substantially rectangular laminates 300 (310) together, and a storage portion 102 formed between the pair of laminates 300 (310) by the sealed portion 101. That is, the side end portion, lower end portion, and upper end portion of the packaging bag 100 are sealed by the sealed portion 101. The packaging bag 100 includes a storage portion 102 in which a packaged item (e.g., food) is stored in a non-sealed portion (sheet portion) surrounded by the sealed portion 101. The sealed portion 101 at the lower end portion may be sealed after the packaged item is filled in the storage portion 102. The seal portion 101 is formed by heat sealing two pieces of the sealant film 20 together.

[0105] It is not essential that the pair of packaging materials constituting the packaging bag 100 have the same layer structure, and for example, the pair of packaging materials may be composed of laminates having different layer structures.

[0106] The packaging bag 100 may be provided with an opening means 120 for facilitating opening. The opening means has a pair of easy-to-open processed parts 124 consisting of V-shaped notches formed in the sealed part 101 at the side end, and a half-cut line 121 that serves as a slitting path between the pair of easy-to-open processed parts 124. The half-cut line 121 can be formed using a laser. The easy-to-open processed parts 124 are not limited to V-shaped notches, and may be U-shaped or I-shaped notches, or may be a group of scars.

[0107] Since the packaging bag 100 includes the laminates 300 and 310, discoloration or peeling of the laminate during heat sealing is sufficiently suppressed. Such a packaging bag 100 can be suitably used as a packaging bag that is likely to be exposed to heat during production. Examples of such packaging bags include zipper bags, standing bags, and gusset bags.

[0108] FIG. 6 is a plan view showing an example of a zipper bag. The zipper bag 500 is, for example, the above-mentioned packaging bag 100 to which a resealing means 501 (for example, a fastener tape) is attached. The resealing means 501 can be formed by sandwiching it between the sealant films 20 of a pair of laminates 300 (310) and heat sealing it. At this time, the end 502 of the resealing means 501 is heat sealed (point sealed) and then the peripheral seal portion 101 is formed. Therefore, more heat is applied to the end 502 than to the peripheral seal portion 101. Therefore, by using the laminates 300, 310 of the present disclosure, discoloration and / or peeling of the laminate due to heat at the end 502 when forming the resealing means 501 of the zipper bag 500 can be reduced, and a zipper bag 500 with good appearance can be produced.

[0109] 7 is a plan view showing an example of a standing bag. Standing bag 400 may be composed of two laminates 300a, 300b forming the side surfaces, laminate 300c (gusset sheet) forming the bottom surface, and internal storage section 102. Standing bag 400 may also include non-sealed section 411 and steam release section 410. The structure of laminates 300a, 300b, 300c may be the same as the structure of laminate 300 shown in FIG. 1. Standing bag 400 has upper end sealed section 401 (sealed section 101) at the upper end, side end sealed sections 403, 404 (sealed section 101) at both side ends, and lower end sealed sections 405, 406 (sealed section 101) at the lower end. The top end seal portion 401 and the side end seal portions 403, 404 are formed by overlapping and heat-sealing the sealant films 20 at the ends of the laminates 300a, 300b.

[0110] On the other hand, the bottom end seal portion 405 (gusset seal portion) is formed by overlapping and heat-sealing the sealant films 20 at the ends of the laminates 300a and 300c, and the bottom end seal portion 406 (gusset seal portion) is formed by overlapping and heat-sealing the sealant films 20 at the ends of the laminates 300b and 300c. At this time, the bottom laminate 300c is folded in half and sandwiched between the side laminates 300a and 300b to heat-seal the four laminates at once. At this time, point sealing may be further performed to prevent leakage. Therefore, when forming the bottom end seal portions 405 and 406, more heat is applied than when two laminates are heat-sealed. Therefore, by using the laminates 300 and 310 of the present disclosure, discoloration and / or peeling of the laminate due to heat when forming the bottom end seal portions 405 and 406 of the standing bag 400 can be reduced, and a standing bag 400 with good appearance can be produced.

[0111] The package 200 includes a packaging bag 100 and an object to be contained in the container 102 of the packaging bag 100. The object to be contained is not particularly limited and may be a solid object, a liquid object, or a mixture thereof. Examples of the object to be contained include food, beverages, medicines, electronic devices, etc.

[0112] <Method of manufacturing packaging bag and packaging body> The procedure for manufacturing the packaging bag 100 and the packaging body 200 using the laminate 300 will be described below. A pair of laminates 300 cut into a predetermined shape is prepared as packaging materials. The sealant films 20 provided on one side of each laminate 300 are placed opposite each other, and the sealant films 20 are bonded to each other. This forms sealed portions 101 at the upper end and side ends, and forms a non-sealed portion surrounded by the sealed portions 101 in a U-shape. In this manner, a packaging bag 110 in which only the upper end (or only the lower end) is unsealed is obtained as shown in FIG. 8. In some examples, the packaging bag of this embodiment may not have a portion of the periphery sealed as shown in FIG. 8.

[0113] Next, the packaged item is filled from the unsealed upper end (or lower end). After that, the laminates 300 are bonded together at the upper end (or lower end) to form a seal portion 101 at the upper end (or lower end). In this manner, a package 200 including a packaging bag 100 and the packaged item contained therein can be manufactured.

[0114] The packaging bag 100 and the packaging body 200 are manufactured using the laminates 300, 310. Therefore, the packaging bag 100 and the packaging body 200 have excellent heat resistance while reducing the environmental impact, and the high degree of freedom in design can increase consumer purchasing motivation.

[0115] Although several examples have been described above, the present embodiment is not limited to the above examples. In addition, the shape of the packaging bag is not limited to a four-sided bag, a zipper bag, a standing bag, and a gusset bag, and may be, for example, a two-sided bag, a three-sided bag, a palm-shaped bag, etc.

[0116] The present disclosure includes the following embodiments and modifications thereof. [1] A laminate comprising a base film, a primer layer, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, The adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof; The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A laminate, in which when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a heat-sealing time of 1.5 seconds, the color difference (ΔE) calculated by the following formula (A) is less than 3.0.

[0117]

number

[10] The laminate according to [9], wherein the content of the trifunctional derivative is higher than the content of the bifunctional derivative.

[11] The laminate according to any one of [1] to

[10] , wherein the adhesive composition contains a surface modifier.

[12] A step of forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition. The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A method for producing a laminate, in which when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a heat-sealing time of 1.5 seconds, the color difference (ΔE) calculated by the following formula (A) is less than 3.0.

[0118]

number

[13] When heat-sealed under the above heat-sealing conditions, the number of discoloration points having a size of 20 μm or more that appear on the printed surface is within 1 mm of the heat-sealed portion. 2 The method for producing a laminate according to

[12] , wherein the number of particles per unit area is 10 or less.

[14] The method for producing a laminate according to

[12] or

[13] , wherein the area ratio of the peeled portion of the laminate generated when heat-sealed under the heat-sealing conditions is 9.0% or less based on the heat-sealed portion.

[15] A step of forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition. The polyisocyanate component includes a derivative of hexamethylene diisocyanate, When heat-sealed under conditions of 220°C, 0.2MPa, and 1.5 seconds, the number of discolored spots with a size of 20μm or more that appear is 1 mm2. 2 A method for manufacturing a laminate, wherein the number of defects is 10 or less per unit area.

[16] A step of forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition. The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A method for manufacturing a laminate in which the area ratio of the peeled portion of the laminate based on the heat seal portion when heated and pressurized under heat seal conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds is 9.0% or less.

[17] A packaging bag, which is constructed by heat-sealing the sealant films in the laminate according to any one of the above [1] to

[11] .

[18] A packaging body comprising the packaging bag described in

[17] above and an item contained in the storage portion of the packaging bag. EXAMPLES

[0119] The present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited to the following examples.

[0120] <Evaluation using color difference (ΔE) as an index> Example 1 [Laminated body production] A commercially available polyethylene terephthalate film (PET film, thickness: 12 μm) was prepared as a substrate film. One side of this PET film was coated with an aqueous primer resin (a resin containing polyethyleneimine, manufactured by Michelman, product name: DP050) to form a primer layer. At this time, the coating amount of aqueous polyethyleneimine was 0.10 to 0.18 g / m 2 The water-based primer resin was applied to the PET film so that the thickness of the water-based primer resin was 100 μm.

[0121] An electrostatic ink composition was applied to the surface of the primer layer using a digital printer (HP Indigo 20000 label and packaging digital printer) to form an electrostatic ink layer. Four types of ink compositions, yellow (Y), magenta (M), cyan (C), and W (white), were prepared, and an electrostatic ink layer was formed so that the ink coverage was Y: 20%, M: 0%, C: 10%, and W: 100%. As the electrostatic ink composition, an electrostatic ink composition (HP Indigo Electroink) containing a thermoplastic resin containing a copolymer of ethylene acrylic acid and ethylene methacrylic acid was used.

[0122] As the polyisocyanate component, a derivative of diphenylmethane isocyanate (MDI) (MDI derivative, manufactured by Mitsui Chemicals, Inc.), a derivative of hexamethylene diisocyanate (HDI derivative I, manufactured by Mitsui Chemicals, Inc.), and a derivative of hexamethylene diisocyanate (HDI derivative II, manufactured by Mitsui Chemicals, Inc.) were prepared. The HDI derivative I contained a bifunctional derivative of hexamethylene diisocyanate. The HDI derivative II contained a trifunctional derivative of hexamethylene diisocyanate. The MDI derivative, HDI derivative I, and HDI derivative II were mixed in a mass ratio of MDI derivative:HDI derivative I:HDI derivative II = 100:14:28 to prepare a polyisocyanate component.

[0123] A polyether polyol (manufactured by Mitsui Chemicals, Inc., product name: XRN-21B) was prepared as the polyol component. The polyol component and the polyisocyanate component were mixed so that the mass ratio of the polyol component to the polyisocyanate component was 142 / 65 (≒2.18), and a surface modifier was further added to prepare an adhesive composition. This adhesive composition was heated to about 60°C and applied to one side of the electrostatic ink layer formed on the substrate film using a roll coater to form a first coating film having a predetermined thickness. The amount of adhesive composition applied was about 2.0 g / m 2 This first coating film and a commercially available nylon film (NY film, manufactured by Kohjin Film & Chemicals Co., Ltd., product name: Bonyl W, thickness: 15 μm) as an intermediate layer were laminated so as to face each other, and the electrostatic ink layer on the base film and the NY film were bonded via the first coating film (adhesive composition) using a nip roll.

[0124] Next, the adhesive composition was similarly applied to the surface of the NY film opposite to the surface to which the base film was attached, to form a second coating film having a predetermined thickness. The amount of the adhesive composition applied was about 2.0 g / m 2 A commercially available linear low-density polyethylene film (LLDPE film, thickness: 100 μm) was laminated as a sealant film on this second coating film so as to face each other, and the NY film and the sealant film were bonded via the second coating film (adhesive composition) using a nip roll.

[0125] Thereafter, aging was performed at 45° C. for 2 days to cure the adhesive composition of the first coating film and the second coating film. In this manner, a laminate having a PET film, a primer layer, an electrostatic ink layer, a first adhesive layer, a NY film, a second adhesive layer, and an LLDPE film in this order was obtained. This was designated as the laminate of Example 1.

[0126] [Heat seal and color difference measurement] Using a spectrophotometer (manufactured by X-rite, product name: eXact), the brightness (L* ), hue and saturation (a * , b * ) was measured.

[0127] Thereafter, the laminate was heated and pressed under heat-sealing conditions of a temperature of 220° C., a pressure of 0.2 MPa, and a time of 1.5 seconds using a heat-sealing device. After the heating and pressing, the lightness (L * ), hue and saturation (a * , b * The above measurements were performed on the same surface and at the same position before and after the application of heat and pressure. The difference in brightness (ΔL * ), the difference in hue and saturation (Δa * , Δb * The color difference (ΔE) was calculated from the above formula (A). The results are shown in Table 1.

[0128] (Examples 2 to 6) A laminate was produced in the same manner as in Example 1, except that the ink coverage was set as shown in Table 1, and ΔE was calculated. The results are shown in Table 1.

[0129] Comparative Example 1 An organic solvent-based adhesive composition with a solid content of 33% by mass was prepared by blending an aliphatic polyester polyol (manufactured by Mitsui Chemicals, Inc., product name: Takelac A626, hereinafter sometimes referred to as "(A)") as a base agent, a polyisocyanate (manufactured by Mitsui Chemicals, Inc., product name: Takenate A65, hereinafter sometimes referred to as "(B)") as a curing agent, and ethyl acetate as a solvent. The blending ratio (mass basis) of each component was (A):(B) = 16:1.

[0130] A primer layer was formed on a substrate film (PET film) in the same manner as in Example 1. Then, an electrostatic ink composition was applied to a part of the surface of the primer layer using a digital printer (Indigo20000 label and packaging digital printer manufactured by HP) to form an electrostatic ink layer. The ink coverage of the electrostatic ink layer was as shown in Table 1.

[0131] The organic solvent-based adhesive composition prepared as described above was applied to the electrostatic ink layer using a dry laminating device, and then hot air drying was performed to form a first coating film consisting of only nonvolatile components. The coating amount of the nonvolatile coating film was about 2.0 g / m 2 This first coating film and the NY film used in Example 1 were overlapped so as to face each other, and the electrostatic ink layer on the base film and the NY film were bonded via the first coating film using a nip roll.

[0132] Furthermore, the above-mentioned organic solvent-based adhesive composition was applied to the surface of the NY film opposite to the surface to which the base film was attached using a dry laminator, and then dried with hot air to form a second coating film consisting only of non-volatile components. The coating amount of the adhesive composition was about 2.0 g / m 2 A commercially available linear low-density polyethylene film (LLDPE film, thickness: 100 μm) was laminated as a sealant film on this second coating film so as to face each other, and the NY film and the sealant film were bonded via the second coating film.

[0133] Thereafter, aging was performed at 40°C for 2 days to cure the first coating film and the second coating film. By such a dry lamination method, a laminate of Comparative Example 1 having a base film, a primer layer, an electrostatic ink layer, a first adhesive layer, a NY film, a second adhesive layer, and a sealant film in this order was obtained. The laminate of Comparative Example 1 differs from the laminate of Example 1 in that an organic solvent-based adhesive composition is used. The ΔE of the laminate of Comparative Example 1 was measured using the same procedure as in Example 1. The measurement results are shown in Table 1.

[0134] (Comparative Examples 2 to 6) A laminate was produced in the same manner as in Comparative Example 1, except that the ink coverage was set as shown in Table 1, and ΔE was calculated. The results are shown in Table 1.

[0135] [Table 1]

[0136] As shown in Table 1, the laminates of Examples 1 to 6 had a sufficiently smaller color difference (ΔE) before and after heating and pressing than those of Comparative Examples 1 to 6. Thus, it was confirmed that the laminates of Examples 1 to 6 were able to sufficiently suppress discoloration caused by heating and pressing.

[0137] <Evaluation using the number of discolored spots as an index> Example 7 The ink coverage of the electrostatic ink composition was set to the ink coverage shown in Example 4 (Y: 70%, M: 40%, C: 10%, W: 100%), and a laminate was produced in the same manner as in Example 4. Heating and pressing were performed under heat sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds. The heat-sealed portion (portion to be heat-sealed) before and after heating and pressing was observed under an optical microscope at 100 times magnification. In an area of ​​1.0 mm x 1.0 mm arbitrarily selected from the observation image, the number of discolored points (circumscribed circle diameter of 20 μm or more) caused by heating and pressing was counted. The results are shown in Table 2.

[0138] Example 8 Heating and pressing were performed in the same manner as in Example 7, except that the heat sealing conditions were a temperature of 230° C., a pressure of 0.2 MPa, and a time of 1.5 seconds, and the number of discolored points caused by heating and pressing was counted in the same manner as in Example 7. The results are shown in Table 2.

[0139] Comparative Example 7 The ink coverage by the electrostatic ink composition was set to the ink coverage shown in Comparative Example 4 (Y: 70%, M: 40%, C: 10%, W: 100%), and a laminate was produced in the same manner as in Comparative Example 4. Heating and pressing were then performed under the same heat sealing conditions as in Example 7. The number of discoloration points that occurred in the heat sealed portion due to heating and pressing was counted in the same manner as in Example 7. The results are shown in Table 2.

[0140] Comparative Example 8 Heating and pressing were performed in the same manner as in Comparative Example 7, except that the heat sealing conditions were a temperature of 230° C., a pressure of 0.2 MPa, and a time of 1.5 seconds, and the number of discolored points caused by heating and pressing was counted in the same manner as in Comparative Example 7. The results are shown in Table 2.

[0141] [Table 2]

[0142] FIG. 9 is an optical microscope photograph showing the surface (the surface on the PET film side) of the laminate of Example 7 after heating and pressing, enlarged by 100 times. FIG. 10 is an optical microscope photograph showing the surface of the laminate of Comparative Example 7 after heating and pressing, enlarged by 100 times. As shown in FIG. 10, in the laminate of Comparative Example 7, discoloration points occurred on the surface due to heat sealing. As shown in Table 2 and FIG. 9, in Examples 7 and 8, almost no discoloration points occurred due to heat sealing. On the other hand, as shown in Table 2 and FIG. 10, in Comparative Examples 7 and 8, many discoloration points occurred due to heat sealing. This confirmed that discoloration occurred.

[0143] From the results of the above-mentioned Examples and Comparative Examples, it was confirmed that discoloration due to heat sealing can be suppressed by using a solventless adhesive composition containing a polyisocyanate component including a derivative of hexamethylene diisocyanate and a polyol component. The factors that contribute to the suppression of discoloration in this way are thought to be the improvement in the strength of the electrostatic ink composition and the improvement in the adhesive strength between each layer. These strength-improving effects are also shown in Examples 12 to 14 and Comparative Example 12 described below.

[0144] <Evaluation using the peeled part of laminate as an index> Example 9 A laminate was produced in the same manner as in Example 1, except that the ink coverage by the electrostatic ink composition was set to Y: 40%, M: 20%, C: 20%, and W: 100%. Heating and pressing were then performed under heat sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, so that the total area of ​​the heat sealed portion was 20 mm x 20 mm.

[0145] Peeling of the laminate that occurred in the heat-sealed area was visually confirmed, and the peeled-off portion of the laminate was observed enlarged under a digital microscope (microscope) to measure the length and width, and the area of ​​the peeled-off portion of the laminate was calculated. The digital microscope used was a "VHX-6000" (manufactured by Keyence Corporation). Three laminates were also produced, and the area of ​​the peeled-off portion of the laminate was calculated for each laminate. In this way, the area (mm 2 The peeled area of ​​the laminate was then multiplied by the total area of ​​the heat-sealed parts (400 mm 2 The area ratio of the peeled part of the laminate was calculated by dividing the area ratio by the area ratio of the peeled part of the laminate. The results are shown in Table 3.

[0146] Example 10 A laminate was produced in the same manner as in Example 1, except that the ink coverage by the electrostatic ink composition was set to Y: 40%, M: 20%, C: 10%, and W: 100%, and the area ratio of the peeled portion of the laminate was measured in the same manner as in Example 9. The results are shown in Table 3.

[0147] Example 11 A laminate was produced in the same manner as in Example 1, except that the ink coverage by the electrostatic ink composition was set to Y: 100%, M: 100%, C: 100%, and W: 100%, and the area ratio of the peeled portion of the laminate was measured in the same manner as in Example 9. The results are shown in Table 3.

[0148] Comparative Example 9 Except for changing the ink coverage rate of the electrostatic ink composition to Y: 40%, M: 20%, C: 20%, and W: 100%, a laminate was prepared in the same manner as in Comparative Example 1, and the area ratio of the peeled portion of the laminate was measured in the same manner as in Example 9. The results are shown in Table 3.

[0149] Comparative Example 10 Except for changing the ink coverage rate of the electrostatic ink composition to Y: 40%, M: 20%, C: 10%, and W: 100%, a laminate was prepared in the same manner as in Comparative Example 1, and the area ratio of the peeled portion of the laminate was measured in the same manner as in Example 9. The results are shown in Table 3.

[0150] Comparative Example 11 Except for changing the ink coverage rate of the electrostatic ink composition to Y: 100%, M: 100%, C: 100%, and W: 100%, a laminate was prepared in the same manner as in Comparative Example 1, and the area ratio of the peeled portion of the laminate was measured in the same manner as in Example 9. The results are shown in Table 3.

[0151] [Table 3]

[0152] Fig. 11 is a photograph of the surface of the laminate of Comparative Example 9 after heating and pressing. As shown in Fig. 11, in the laminate of Comparative Example 9, peeled parts L of the laminate were generated after heat sealing. The areas of the peeled parts of the laminate in Examples 9 to 11 were smaller than those in Comparative Examples 9 to 11, and the area ratios of the peeled parts of the laminate were also smaller. Therefore, it was shown that the laminates of Examples 9 to 11 have higher heat resistance when heat sealed than the laminates of Comparative Examples 9 to 11.

[0153] <Evaluation of adhesive strength and sealing strength> Example 12 [Laminated body production] Using the same procedure as in Example 1, a primer layer was formed on one side of the PET film used in Example 1, and multiple electrostatic ink layers were formed on the surface of the primer layer and the primer layer so that the ink coverage was 0% (plain), 100% (white (W): 100%), 200% (cyan (C): 100% + white (W): 100%), 300% (magenta (M): 100% + yellow (Y): 100% + white (W): 100%), and 400% (cyan (C): 100% + magenta (M): 100% + yellow (Y): 100% + white (W): 100%).

[0154] A solventless adhesive composition was prepared in the same manner as in Example 1, except that no surface modifier was added. In the same manner as in Example 1, the adhesive composition was applied to the surface of the electrostatic ink layer (or primer layer) to form a first coating film. The NY film used in Example 1 was adhered to the electrostatic ink layer (or primer layer) via the first coating film, and then the LLDPE film used in Example 1 was adhered to the NY film via the second coating film. Thereafter, the first coating film and the second coating film were cured in the same manner as in Example 1, and a laminate having a PET film, a primer layer, an electrostatic ink layer, a first adhesive layer, a NY film, a second adhesive layer, and an LLDPE film in this order was obtained.

[0155] [Adhesive strength measurement] The adhesive strength of the prepared laminate was measured in accordance with JIS K 6854-1:1999. Specifically, the prepared laminate was cut into a width of 15 mm to obtain measurement samples with ink coverage of 0%, 100%, 200%, 300%, and 400%. After peeling between the PET film and the NY film at the end of the measurement sample, the peel adhesion strength of the laminate was measured using a tensile tester under conditions of an angle of 90°, a tensile speed of 300 mm / min, and room temperature. This peel adhesion strength was taken as the adhesive strength. In addition, the peel adhesion strength between the NY film and the LLDPE film was measured in the same manner as the adhesive strength of the second adhesive layer. The measurement results are shown in Table 4.

[0156] [Seal strength measurement] A pair of laminated sealant films (LLDPE films) having the same ink coverage were overlapped and heat-sealed to form a heat-sealed portion. The heat-sealing conditions were 180°C, 0.2 MPa, and 0.5 seconds. The LLDPE film was welded in this manner to prepare a measurement sample with a width of 15 mm. Measurement samples were prepared with ink coverage rates of 0%, 100%, 200%, 300%, and 400%, respectively. The seal strength of the seal portion of the measurement sample prepared was measured in accordance with JIS K 7127:1999. The measurement was performed using a tensile tester under the conditions of a peel angle of 90°, a tensile speed of 300 mm / min, and room temperature (20°C), to measure the peel strength between the heat seals. This peel strength was taken as the seal strength. The measurement results were as shown in Table 4.

[0157] Comparative Example 12 Laminates were produced in the same manner as in Example 12, except that the organic solvent-based adhesive layer of Comparative Example 1 was used instead of the solvent-free adhesive composition used in Example 12, and the electrostatic ink layer (or primer layer) on the PET film was bonded to the NY film, and the NY film was bonded to the LLDPE film by the same dry lamination method as in Comparative Example 1. The adhesive strength and seal strength were measured in the same manner as in Example 12. The measurement results are shown in Table 4.

[0158] (Example 13) A laminate was produced in the same manner as in Example 12, except that a commercially available aluminum foil (manufactured by Luoyang Wanji Aluminum Processing Co., Ltd., product number: 8079, thickness: 7 μm) was used as the intermediate layer, and a commercially available low-density polyethylene film (LDPE film, manufactured by Tamapoly Co., Ltd., product name: V-1, thickness: 60 μm) was used as the sealant film. The adhesive strength and seal strength were measured in the same manner as in Example 12. The measurement results are shown in Table 4.

[0159] Example 14 An adhesive composition containing the surface modifier used in Example 1 was prepared. A laminate was produced in the same manner as in Example 13, except that the adhesive composition containing the surface modifier was used. The adhesive strength and seal strength were measured in the same manner as in Example 13. The measurement results are shown in Table 4.

[0160] [Table 4]

[0161] In Table 4, the numerical values ​​in the columns for Examples 12, 13, and 14, and Comparative Example 12 indicate adhesive strength or seal strength. The column below each numerical value indicates the location of peeling when each strength was measured. "PET cut" indicates that the PET film was cut. "Ink / Ad" indicates that the interface between the electrostatic ink layer and the first adhesive layer was peeled off. "NY / Ad" indicates that the interface between the NY film and the second adhesive layer was peeled off. "Ink cohesion" indicates that the electrostatic ink layer itself was broken, and "Ad cohesion" indicates that the first adhesive layer itself was broken. "Ad / AL" indicates that the first adhesive layer was peeled off between the aluminum foil, and "AL / Ad" indicates that the aluminum foil was peeled off between the second adhesive layer. "Edge cut" indicates that the laminate was broken at the edge of the seal portion, and "triangular peeling" indicates that peeling occurred within the laminate, not between the sealant layers.

[0162] The laminate of Example 12, at least in the portion where the electrostatic ink layer was provided, had higher adhesive strength and seal strength than the laminate of Comparative Example 12. From a comparison between Examples 13 and 14, it was confirmed that the adhesive strength was significantly increased by using a surface modifier.

[0163] From the results of each example and each comparative example, it was confirmed that the laminate of the present disclosure has high heat resistance when a solvent-free adhesive composition is used. Furthermore, it was confirmed that it has sufficiently high adhesive strength and seal strength. Therefore, the laminate of the present disclosure has excellent heat resistance, adhesive strength, and seal strength, and can be suitably used for packaging bags and packages. [Industrial Applicability]

[0164] According to the present disclosure, it is possible to provide a laminate having an electrostatic ink layer, which has excellent heat resistance while reducing the environmental impact, and a manufacturing method thereof. It is also possible to provide a packaging bag and a packaging body including such a laminate. [Explanation of symbols]

[0165] 10...base film, 20...sealant film, 21...intermediate layer, 30...adhesive layer (first adhesive layer), 31...adhesive layer (second adhesive layer), 40...primer layer, 50, 51...electrostatic ink layer, 52...printed surface, 53...halftone dot, 55...discoloration point, X...heat seal portion, L, L1, L2, L3...peel-off portion of laminate, 100, 110...packaging bag, 101...seal portion, 102...container Container portion, 120...opening means, 121...half-cut line, 124...easy-open processing portion, 200...package, 300, 310...laminated body, 300A...surface, 400...standing bag, 401...upper end sealed portion, 403, 404...side end sealed portion, 405, 406...lower end sealed portion, 410...steam vent portion, 411...non-sealed portion, 500...zipper bag, 501...resealing means, 502...end portion.

Claims

1. A laminate comprising a substrate film, a primer layer, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, The adhesive layer comprises a solventless adhesive composition containing a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof; The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A laminate, in which when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a heat-sealing time of 1.5 seconds, the color difference (ΔE) calculated by the following formula (A) is less than 3.

0. [0010] [In the above formula (A), ΔL * indicates the difference in brightness before and after heating and pressing under the heat sealing conditions, and Δa * and Δb * indicates the difference in hue and chroma before and after heating and pressing under the heat sealing conditions.

2. When heat-sealed under the above heat-sealing conditions, the number of discoloration points having a size of 20 μm or more that appear on the printed surface is within 1 mm of the heat-sealed portion. 2 2. The laminate of claim 1, wherein the number of particles per unit area is 10 or less.

3. 2. The laminate according to claim 1, wherein the area ratio of peeled portions of the laminate, which occurs when the laminate is heat-sealed under the heat-sealing conditions, is 9.0% or less based on the heat-sealed portion.

4. A laminate comprising a substrate film, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, The adhesive layer includes a solventless adhesive composition including a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof; The polyisocyanate component includes a derivative of hexamethylene diisocyanate, When the sealant film is heat-sealed under heat and pressure conditions of a temperature of 220° C., a pressure of 0.2 MPa, and a heat-sealing time of 1.5 seconds, the number of discoloration points having a size of 20 μm or more that are generated is determined to be within 1 mm of the heat-sealed portion. 2 10 or less per stack.

5. A laminate comprising a substrate film, an adhesive layer, and a sealant film in this order, and a printed surface of an electrostatic ink composition adhered to the adhesive layer, The adhesive layer includes a solventless adhesive composition including a polyol component and a polyisocyanate component, a cured product thereof, or a mixture thereof; The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A laminate in which, when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds, the area ratio of the peeled portion of the laminate based on the heat-sealed portion is 9.0% or less.

6. The laminate according to any one of claims 1 to 5, wherein the polyisocyanate component further contains a polyisocyanate different from the derivative of hexamethylene diisocyanate.

7. The laminate according to any one of claims 1 to 5, wherein a mass ratio of the polyisocyanate component to the polyol component is 1 or more.

8. The laminate according to any one of claims 1 to 5, wherein the polyol component contains a polyether polyol.

9. The laminate according to any one of claims 1 to 5, wherein the derivative of hexamethylene diisocyanate includes a bifunctional derivative of hexamethylene diisocyanate and a trifunctional derivative of hexamethylene diisocyanate.

10. The laminate according to claim 9 , wherein the content of the trifunctional derivative is higher than the content of the bifunctional derivative.

11. The laminate according to any one of claims 1 to 5, wherein the adhesive composition contains a surface modifier.

12. forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition. The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A method for producing a laminate, wherein when the sealant film is heat-sealed by heating and pressurizing under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a heat-sealing time of 1.5 seconds, the color difference (ΔE) calculated by the following formula (A) is less than 3.

0. [0025] [In the above formula (A), ΔL * indicates the difference in brightness before and after heating and pressing under the heat sealing conditions, and Δa * and Δb * indicates the difference in hue and chroma before and after heating and pressing under the heat sealing conditions.

13. When heat-sealed under the above heat-sealing conditions, the number of discoloration points having a size of 20 μm or more that appear on the printed surface is within 1 mm of the heat-sealed portion. 2 The method for producing a laminate according to claim 12, wherein the number of particles per unit area is 10 or less.

14. The method for producing a laminate according to claim 12 or 13, wherein an area ratio of peeled parts of the laminate produced when heat-sealed under the heat-sealing conditions is 9.0% or less based on the heat-sealed part.

15. forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition. The polyisocyanate component includes a derivative of hexamethylene diisocyanate, When heat-sealed under conditions of 220°C, 0.2 MPa, and 1.5 seconds, the number of discoloration points with a size of 20 μm or more that appear is within 1 mm of the heat-sealed area. 2 The method for producing a laminate, wherein the number of defects is 10 or less per unit area.

16. forming a primer layer on one side of a substrate film; printing an electrostatic ink composition on the primer layer to obtain a printed surface; a step of adhering the printed surface and a substrate including a sealant film using a solventless adhesive composition including a polyisocyanate component and a polyol component; and curing or semi-curing the adhesive composition. The polyisocyanate component includes a derivative of hexamethylene diisocyanate, A method for producing a laminate, in which the area ratio of the peeled portion of the laminate based on the heat-sealed portion when heated and pressurized under heat-sealing conditions of a temperature of 220°C, a pressure of 0.2 MPa, and a time of 1.5 seconds is 9.0% or less based on the heat-sealed portion.

17. A packaging bag formed by heat-sealing the sealant films in the laminate according to any one of claims 1 to 5.

18. A package comprising the packaging bag according to claim 17 and an item contained in a container portion of the packaging bag.

Citation Information

Patent Citations

  • Two pack curable solvent-free adhesive

    JP2011162656A

  • flexible packaging material

    JP2018530478A

  • Laminate and its manufacturing method, packaging bag as well as package

    JP2022102513A

  • Curing agent, two-component adhesive, adhesive composition, cured product, laminate and method for producing same, packing material, and packed body

    WO2021024981A1